CHANGES IN SYMPATHETIC ACTIVITY IN PATIENTS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Dhillon, Sukhjinder Kaur; Kaur, Narinder; Arora, Dimple Bajaj; Sandhu, Parminder (Pakistan Journal of Physiology, 2018)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a major cause of disability and death all over the world. Alteration in autonomic activity has been consistently found in COPD. This study was done to see changes in sympathetic activity in patients of COPD. Methods: The study was carried out on 60 male COPD patients and 60 healthy subjects as controls. Heart rate, respiratory rate, pulse, and temperature were recorded in healthy subjects and patients. For testing sympathetic activity blood pressure variation on standing and lying down, Cold Pressor Test (CPT) and Hand Grip Test (HGT) were performed. Results: The mean rise in systolic blood pressure (SBP) in response to CPT was statistically significant in COPD patients as compared to normal subjects. The variation in diastolic blood pressure (DBP) in response to HGT was statistically significant as compared to controls. The mean fall of systolic blood pressure in response to standing in COPD patients was statistically significant. Conclusion: There is significantly increased sympathetic nervous system activity in COPD patients compared to that in normal, healthy subjects. Pak J Physiol 2016;12(4):9–11